2012
DOI: 10.3109/1547691x.2012.696743
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity of the organochlorine pesticide methoxychlor in female ICR, BALB/c, and C3H/He mice

Abstract: Several types of pesticides, including organochlorines, are known to suppress or modulate immune responses. The present study evaluated the immunotoxicity of the organochlorine pesticide methoxychlor (MXC) in female BALB/c, C3H/He, and ICR mice. Mice were given oral MXC doses of 0, 30, 100, and 300 mg/kg each day for 7 consecutive days. On day 4, the mice also received an intravenous injection of sheep red blood cells (SRBC). The splenic plaque-forming cell (PFC) IgM response and the serum anti-SRBC IgM antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…While previous studies reported that pesticides could affect immunity through different mechanisms (Badesha et al 1995;Li et al 2002;Li 2007), immune suppression/dysregulation is a major mechanism by which pesticides exert their immunomodulatory activity, affect immunocompetence and consequently increase host susceptibility to diseases and an array of immune disorders (Hayashi et al 2013). Although CPF and CBZ belong to two different families (organophosphates vs. carbamates), they each act as potent immunosuppressants in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies reported that pesticides could affect immunity through different mechanisms (Badesha et al 1995;Li et al 2002;Li 2007), immune suppression/dysregulation is a major mechanism by which pesticides exert their immunomodulatory activity, affect immunocompetence and consequently increase host susceptibility to diseases and an array of immune disorders (Hayashi et al 2013). Although CPF and CBZ belong to two different families (organophosphates vs. carbamates), they each act as potent immunosuppressants in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, humans and animals are constantly exposed either accidentally or professionally to these biologically active molecules. Although, the widespread use of pesticides provides great benefits to optimize agricultural productivity for the growing world population, their ubiquitous presence constitutes an adverse health risk for human and animals (Hayashi et al 2013). Indeed, it is widely accepted that, pesticides represent a major public health problem worldwide because of their deleterious pronounced effects on humans and animals (de Souza et al 2011;Mostafalou & Abdollahi 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that methoxychlor is able to inhibit antibody production in rodent models (Chapin et al 1997;Hayashi et al 2013), indicating potential toxicity to the adaptive immune system. However, in the zebrafish RBA, methoxychlor inhibited the respiratory burst, indicating this agent also impacts innate immunity.…”
Section: Compounds Both Developmentally Toxic and Immunotoxicmentioning
confidence: 98%
“…Therefore, human and animal were constantly exposed to their adverse risk. Although, fungicides are designed to play beneficial role in enhancing agricultural products and controlling infectious and vector diseases, they acted as potent mutagenic, teratogenic, and carcinogenic compounds on animal and human 4,5 …”
Section: Introductionmentioning
confidence: 99%